1996
DOI: 10.1097/00005792-199609000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Polymyositis as a Manifestation of Chronic Graft-Versus-Host Disease

Abstract: A syndrome indistinguishable from idiopathic polymyositis occurred in 11 patients as a manifestation of chronic GVHD. All patients had elevation of creatine phosphokinase (CPK). Immunohistology demonstrated the effector cells in the muscle infiltrates as cytotoxic T cells, a finding similar to idiopathic polymyositis. Polymyositis is a rarely reported complication of chronic graft-versus-host disease (GVHD) with only 8 cases described in the literature. We encountered this syndrome in a small but significant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 14 publications
4
59
2
Order By: Relevance
“…Janin et al 7 reported that 14 out of 475 patients (2.9%) who underwent Allo-BMT from an HLA-identical sibling donor developed fasciitis. Parker et al 10 also showed that the rate of polymyositis among patients who developed chronic GVHD after Allo-BMT from a sibling donor was 3.4%. In this study, only one patient, who underwent R-BMT from an HLA-single locus mismatched donor, developed fasciitis out of 645 R-BMT recipients.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Janin et al 7 reported that 14 out of 475 patients (2.9%) who underwent Allo-BMT from an HLA-identical sibling donor developed fasciitis. Parker et al 10 also showed that the rate of polymyositis among patients who developed chronic GVHD after Allo-BMT from a sibling donor was 3.4%. In this study, only one patient, who underwent R-BMT from an HLA-single locus mismatched donor, developed fasciitis out of 645 R-BMT recipients.…”
Section: Discussionmentioning
confidence: 98%
“…7 In myositis, some reported cases showed a recurrence with either a reduction or cessation of immunosuppressant therapy. [10][11][12]20 One of our patients also had recurrent acute myositis after CsA was tapered, and achieved a second remission of polymyositis with CsA. 20 We need to recognize that both fasciitis and myositis caused by chronic GVHD can result in disabilities that reduce the patient's QOL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common presenting symptoms are moderate to severe proximal muscle weakness and myalgias. 11 Lower extremities seem to be more commonly involved. 15,26,27 Other signs and symptoms may include fever, 2,20,27,28 contractures, 2,18,23,26 dysphagia 14,24 eosinophilia 13,21 and skin induration over the areas of muscle involvement.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] We report two cases of chronic GVHD presenting with polymyositis manifestations 13 and 19 months after allogeneic hematopoietic stem cell transplant, successfully treated with corticosteroids and tacrolimus.…”
mentioning
confidence: 99%